Comparative study of alginate and type I collagen as biomaterials for cartilage stem/progenitor cells to construct tissue-engineered cartilage in vivo - Zhang, Xiaodie; Qi, Lin; Chen, XiaoGang; Lai, Yongxian; Liu, Kai; Xue, Ke (Frontiers in Bioengineering and Biotechnology, 2023)
With the help of biomaterials, cartilage stem/progenitor cells (CSPCs) derived from cartilage tissue present a promising choice for cartilage regeneration. In our previous study, we investigated whether CSPCs could be ideal seeding cells for cartilage tissue regeneration. Biomaterials are fabricated to accelerate tissue regeneration, providing a suitable environment for cell attachment, proliferation, and differentiation. Among the biomaterials used in cartilage regeneration medicine, alginate and collagen are classified as natural biomaterials and are characterized by high biocompatibility, bioactivity, and non-toxic degradation products. However, it is unclear which material would have a competitive advantage in CSPC-based cartilage regeneration in vivo. In the present study, we employed alginate and type Ⅰ collagen as substrates for CSPCs to fabricate tissue-engineered cartilage. Hematoxylin and eosin (HE) staining, Safranin O, immunohistochemical assay, and quantitative real-time polymerase chain reaction (qRT-PCR) were used to evaluate the tissue-engineered cartilage in vivo. Compared with the alginate group, collagen enhanced the expression of cartilage-specific genes, such as ACAN, SOX9, and COLII, more markedly. Furthermore, the marker genes of expression, dedifferentiation, and hypertrophy, COLI and COLX, were downregulated in the collagen group. The results demonstrated that collagen as a substrate was superior to alginate in increasing the accumulation of cartilage-like ECM for CSPCs in vivo. In summary, collagen hydrogel is an effective biomaterial for CSPC-based cartilage regeneration.